Pereira Diamond: benefits management framework - Teixeira, C. (2015)
Nowadays organizations are challenged daily to keep their business running by continuously adding value to its stakeholders in a sustainable way. In order to achieve that, business managers are required to have a clear organizational vision, mission and a well-established business strategy combined with a set of portfolio of projects towards converting strategic goals into business value. Although this is a clear concern in the most of management and executive teams, the majority of them are unable to identify the benefits each initiative will deliver neither how much they represent moneywise, easily leading to a complete “investment-in-failure”. The crisis context together with the huge speed of technology advancements, the power of social networking and market globalization are triggering organizations to rationalize and optimize their resources while business managers are pressurized to deliver successful results. Another concern is the fact business managers are getting “tempted” to tighten their budgets and follow a cost-control management approach as it turns to be the most immediate way to get a positive impact on the P&L. However, in a long term, it will compromise the organization growth and the ability to create sustainable wealth to the stakeholders. This is where capital investments play a key role to support innovative initiatives’ implementation which explains the worldwide increase budget available for new investments, the capital expenditure (capex). But even though new project proposals justify the need of increasing funds, why do most of projects still fail on delivering results? Despite the well advanced project management techniques to manage projects efficiently (triple constraint criteria: scope, budget and time) are organizations selecting the most valuable projects? If resources are not infinite, organizations must follow a reliable appraisal model to select the initiatives that will deliver the most valuable return on investment. The ability to solve a market need with a high value for money within the time-to-market is essential, so knowing what, when and how to invest following a rigorous approach is becoming an essential business skill across every business sector. Since projects are investments which intend to maximize return then business cases and benefits management are a powerful tool to support top management decisions. This paper presents the conceptual basis, perspectives and guidelines for effective project investments, based on the worldwide best practices for business cases. Besides the literature reviews and studies collected to date about this subject, the final conclusions presented are sustained on the results collected from a sample of companies across different sectors who were invited to participate on this research. This research suggests that the Pereira Diamond approach to benefits management has a strong contribution to successfull investment decisions towards the maximization of the return on investment hence the value creation to the business stakeholders.